2013
DOI: 10.1007/s00265-013-1484-y
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen-induced hatching and population-specific life-history response to waterborne cues in brown trout (Salmo trutta)

Abstract: Hatching is an important niche shift, and embryos in a wide range of taxa can either accelerate or delay this life-history switch in order to avoid stage-specific risks. Such behavior can occur in response to stress itself and to chemical cues that allow anticipation of stress. We studied the genetic organization of this phenotypic plasticity and tested whether there are differences among populations and across environments in order to learn more about the evolutionary potential of stress-induced hatching. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 67 publications
3
55
0
Order By: Relevance
“…However, we found little evidence of non-additive genetic variance, and rather observed that these traits harbored significant additive genetic variance. Significant genetic variability in fitness traits was previously found in brown trout [56], [57], [88] and other species [e.g. 19], [65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we found little evidence of non-additive genetic variance, and rather observed that these traits harbored significant additive genetic variance. Significant genetic variability in fitness traits was previously found in brown trout [56], [57], [88] and other species [e.g. 19], [65].…”
Section: Discussionmentioning
confidence: 99%
“…We thus chose to simulate an ecologically relevant situation by inoculating a subset of embryos with the opportunistic fish pathogen, P. fluorescens , to measure the effect of infection on a suite of fitness-related traits. This bacterium is abundant in the aquatic environment [51], which is considered the principle reservoir of infection [52], and has been implicated in disease pathologies not only in adult fish [53], but also in whitefish [54], [55] and more recently in brown trout embryos [56]. Our design allowed us to disentangle variance components and compare the effects of outcrossing with sire and dam effects on offspring phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Brown trout Salmo trutta L. 1758 were sampled in November from five different locations, including the River Aare and four of its tributaries as described in Pompini et al . (). Gametes stripped from the adults were used for full‐factorial in vitro fertilizations (methods described in von Siebenthal et al ., ) each in order to maximize the genetic diversity within the F1 (details in Supporting Information Table SI).…”
Section: Maternal Paternal and Treatment (Warm V Cold Water) Effectmentioning
confidence: 97%
“…They are also able to perceive waterborne cues from microbial infections and to switch life history strategies accordingly (Wedekind ; Pompini et al . ).…”
Section: Introductionmentioning
confidence: 97%